VISUAL MERCHANDISING AND ITS ROLE IN TRADE MARKETING: CAPTURING CONSUMER ATTENTION - Mamatkulova Shoira Djalolovna (Web of Journals Publishing, 2024)
This article examines the critical role of visual merchandising in trade marketing, highlighting its ability to capture consumer attention and influence purchasing decisions. By strategically using elements such as product placement, store layout, color schemes, lighting, and point-of-sale (POS) materials, brands can create an engaging in-store environment that enhances the shopping experience and drives higher sales. The article also examines how digital innovations such as augmented reality and interactive displays are transforming traditional visual merchandising, offering new ways to engage consumers. Using real-world examples, the article illustrates how effective visual merchandising can optimize retail space, increase brand awareness, and improve overall marketing effectiveness.
Keywords: Visual merchandising, trade marketing, consumer attention, store layout, POS materials, shopping experience, retail design, brand awareness, consumer engagement, in-store promotions.